Service selection and switching decisions: user behavior in high-interoperability environments - Johannes Pecher; Emmanuel Syrmoudis; Jens Grossklags (Humanities & Social Sciences Communications)
Abstract Current legislation and market dynamics require and encourage systems to become more open and interoperable. Given this shift, the challenge arises as to how service providers can navigate such environments and whether and how known platform economics are affected by that change. In this context, our work investigates behavior when users interact with services in highly interoperable environments, examining the influence of service attributes and platform economics on service selection and switching decisions, with a focus on the role of transaction cost and time, onboarding time, privacy, ownership, and community. For this purpose, we designed and conducted an extensive survey study with more than 500 respondents that combined a conjoint study with an experimental part on switching scenarios. Our findings suggest that transaction features such as cost, time, and privacy are the main factors in service selection with part-worth utilities being 2.1 to 14.7 times higher than non-transactional features. Additionally, building a strong community and offering ownership opportunities to users are effective strategies for customer retention. Further, we observe that rational choice theory does not explain switching decisions in many cases. Our study has important implications for both industry practitioners and policymakers. Practitioners can use our results to carefully manage effective customer retention strategies, while policymakers can use them to better regulate digital markets.